Study of sulphide stress corrosion behaviour of steel - Tan, Denise Yin Xuan. (2012)
The continuing problem of Sulphide Stress Cracking (SSC) in sour oil and gas exploration is a major concern to the oil and gas industries. SSC usually occurs on materials in corrosive Hydrogen Sulphide (H2S) - containing environments.